DISFUNGSI PENGELOLAAN KAMPUS PURNAMA UNIVERSITAS RIAU DALAM URUSAN PENDIDIKAN TINGGI DI KOTA DUMAI TAHUN 2014-2017 - Akbar, Hapis; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
University of Riau is one of the State Universities in Riau, University of Riau is a State University that has locations in two places, one of which is Purnama University University of Riau which is located in Dumai City which has been in existence since 1994 and used until 2006, in In 2006, the campus activities moved in Pekanbaru City at the same time the campus was not used so it was abandoned, this study aimed, identified and explained the causes of the dysfunction of the management of the Puranama Campus in Riau University in matters of higher education. And identify and explain the obstacles in managing the Purnama University of Riau Campus in higher education matters. This study uses the theory of optimization processes in management by M. Yusuf. this study uses a qualitative approach. Data collection of interviews and documents after being collected is analyzed qualitatively. The results of the discussion showed that the first task was not carried out by the head of the Higher Education Service Institution or Chancellor of the University of Riau in the implementation of facilities to improve the quality of higher education in their work areas. the legal basis is maximally especially in the field of campus supervision and maintenance, the potential possessed by the University of Riau's Purnama Campus which cannot yet be maximized is part of the constraint, then the ability of human resources is also an obstacle related to the management of Purnama University in Riau.Keywords: management dysfunction, higher education, Purnama Campus and University of Riau